Detection of different classes moving object in public surveillance using artificial neural network (ANN) - Rashidan, M. Ariff; Mohd Mustafah, Yasir; Abdul Hamid, Syamsul Bahrin; Zainuddin, N. Afiqah; A. Aziz, Nor Nadirah (2014)
Public surveillance monitoring is rapidly finding its way into Intelligent Surveillance Systems. Street crimes such as snatch theft is increasing drastically in recent years, cause a serious threat to human life worldwide. In this paper, a moving object detection and classification model was developed using novel Artificial Neural Network (ANN) simulation with the aim to identify its suitability for different classes of moving objects, particularly in public surveillance conditions. The result demonstrated that the proposed method consistently performs well with different classes of moving objects such as, motorcyclist, and pedestrian. Thus, it is reliable to detect different classes of moving object in public surveillance camera. It is also computationally fast and applicable for detecting moving objects in real-time.